2017
DOI: 10.1021/acs.inorgchem.7b01730
|View full text |Cite
|
Sign up to set email alerts
|

Three-Fold-Symmetric Selenium-Donor Metallaboratranes of Cobalt and Nickel

Abstract: A novel selenium-containing pyridazinyl-based soft scorpionate ligand (KTnse) was synthesized. It reacts with CoCl and NiCl, yielding the first metallaboratrane complexes with selenium in their donor positions. Further substitution with Ag(OTf) or NaN allows isolation of the respective triflate or azide complexes. Reaction with Ag(OTf) leads in the case of nickel to a dinuclear, dicationic complex with a short Ni-Ni distance, while cobalt gave a mononuclear cationic species. Substitution of the chloride by azi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…In 2008, we suggested that this new set of ligands be termed “flexible scorpionates” [ 6 , 7 ] since the consequences of this extra atom in each of the heterocycles change their properties and potential reactivity quite significantly [ 8 , 9 , 10 ]. A range of heterocycles has now been utilized to generate flexible scorpionate ligands based on sulfur [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ], nitrogen [ 17 , 18 , 19 , 20 , 21 ], phosphine [ 22 , 23 ], oxygen [ 24 , 25 ] and other donors [ 26 , 27 ]. To the best of our knowledge, there are only a small number of complexes reported containing nitrogen-based flexible scorpionate ligands.…”
Section: Introductionmentioning
confidence: 99%
“…In 2008, we suggested that this new set of ligands be termed “flexible scorpionates” [ 6 , 7 ] since the consequences of this extra atom in each of the heterocycles change their properties and potential reactivity quite significantly [ 8 , 9 , 10 ]. A range of heterocycles has now been utilized to generate flexible scorpionate ligands based on sulfur [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ], nitrogen [ 17 , 18 , 19 , 20 , 21 ], phosphine [ 22 , 23 ], oxygen [ 24 , 25 ] and other donors [ 26 , 27 ]. To the best of our knowledge, there are only a small number of complexes reported containing nitrogen-based flexible scorpionate ligands.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, it has been a matter of particular interest as to whether neutral, tricoordinate boron compounds can serve as electron-donating ligands rather than pure acceptor ligands, as they are commonly viewed. Notably, a majority of tricoordinate boron compounds of the type BR 3 are known to act as Lewis acids and σ-accepting or Z-type ligands in transition-metal complexes. By manipulation of the R substituents in BR 3 , it is possible to cause a dramatic change in these properties: formally anionic substituents, such as hydrides, alkyls, aryls, halogenides, and most anionic N-heterocycles lead to classical Lewis acids or Z-type ligands. , In these cases, the vacant p z -orbital of the trigonal planar boron compound is stabilized either by π-donation of the substituents or by dimerization and the formation of two-electron, three-center bonds. Replacing one of the substituents R on boron by a neutral σ-donating and π-accepting substituent L formally results in a partially filled p z -orbital at the boron atom in BR 2 L. This ligand-stabilized boryl ligand acts as an X-type ligand and contributes one electron to a covalent bond.…”
Section: Introductionmentioning
confidence: 99%
“…The respective metal complexes are generally referred to as metallatranes and specifically with boron as metallaboratranes. Many borane ligands with various structural motifs capable for boratrane formation were developed including nitrogen, sulfur, selenium, or phosphorus donor sites. , Typically, such metallaboratrane complexes can either be formed by direct reaction of the respective neutral borane [Me 2 P­(CH 2 ) 2 ] 3 B or [ o -(R 2 P)­C 6 H 4 ] 3 B with a metal precursor or via the more general reaction of a hydroborate ligand HB­(Het) 3 ¯ (Het = 2-thiomethimidazole, 7-azaindol, 2-thiopyridine, 5-thiotriazol, 6- tert -butyl-3-thiopyridazine) ,,, with a metal precursor under elimination of the hydride at boron (Figure ).…”
Section: Introductionmentioning
confidence: 99%
“…49 We have recently developed thiopyridazine-based borate ligands K[HB(Pn R,tBu ) 3 ] (KTn R,tBu ) which form boratrane complexes with metal halide precursors (as shown in Scheme 1). 27,30,34,35,41,50 Thiopyridazine belongs to the electrondeficient heterocycles and is thus expected to promote a strong Z-type interaction. Our observed high tendency for boratrane formation goes along with this expectation.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation